National Amil Zakat Agency as a Moderation of Perception and Religion on the Decision to Pay Zakat - Hardana, Ali; Nasution, Jafar; Damisa, Arti (Goodwood Publishing, 2025)
Purpose: The purpose of this study is to identify the variables that affect muzakis' zakat payment decisions at the National Amil Zakat Agency. Altruism was included in this study as a moderating variable as well. Muzaki's capacity to decide to pay zakat is a result of his attention to and awareness of doing so. Muzaki may decide to distribute zakat at the National Amil Zakat Agency (BAZNAS). Methodology/approach: The population in this study is the entire community in Indonesia, with purposive sampling used to select specific respondents. The sample size was determined using the